PENGARUH CORPORATE SOCIAL RESPONSIBILITY, LIKUIDITAS, DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK - Elok Kurniawati (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
Tax aggressiveness is an action carried out with the aim of minimizing the number of estimated tax costs. The act of tax aggressiveness is mostly carried out by large companies in Indonesia because taxes are considered as costs that have a significant effect on the company and have a direct impact on profitability. The purpose of this study was to analyze the effect of corporate social responsibility, liquidity, and leverage on tax aggressiveness in mining companies listed on the Indonesia Stock Exchange for the period 2014-2017.Sampling using a purposive sampling method. The method of analysis used in this study is multiple linear regression.